(untitled) (Central Asian Journal of Medical Sciences, 2025)
Objective: Post-operative cognitive dysfunction (POCD) is a prevalent consequence of general anesthesia in older individuals (≥60 years) undergoing spine surgery. Factors associated with spinal surgery (prone positioning, prolonged length, and increased bleeding) along with general anesthesia elevate the risk of postoperative complications. Stellate ganglion block (SGB) exhibits neuroprotective effects via enhancing cerebral microcirculation and decreasing inflammation. This study intends to investigate the influence of bilateral SGB on POCD in these patients. Methods: One hundred fourteen elderly spine surgery patients were randomly assigned to a control group (standard general anesthesia) and a study group (ultrasound-guided bilateral SGB 2 hours pre-anesthesia plus general anesthesia). Cognitive function was evaluated by the MMSE/MoCA at T0 (pre-SGB), T1 (one day post-operation), and T3 (three days post-operation); POCD was categorized by severity. Results: One hundred patients were analyzed (14 excluded). Baseline characteristics were similar between groups (p> 0.05). At 2 hours post-op, no difference was found in cognitive impairment between groups. However, the SGB group had fewer moderate and severe cognitive dysfunction cases (p< 0.05). At 72 hours, no difference in mild cognitive impairment was observed, but the SGB group had lower POCD incidence (p< 0.05). Conclusions: Ultrasound-guided bilateral SGB before anesthesia successfully diminishes moderate-to-severe postoperative cognitive dysfunction within 3 days post-operation in elderly spine surgery patients.